2007
DOI: 10.1159/000106684
|View full text |Cite
|
Sign up to set email alerts
|

Physical Examination and ECG Screening in Relation to Echocardiography Findings in Young Healthy Adults

Abstract: Background and Aims: Cardiovascular screening in young adults is an important tool in many occupational settings. Our aim was to test whether screening physical examination and ECG influence the rate of abnormal echocardiogarphic findings in young healthy subjects. Methods: Consecutive echocardiography results of 18- to 20-year-old flight candidates were analyzed retrospectively. Echocardiographies were performed as part of a screening protocol, which includes ECG, physical examination and referral for echocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…A study by van der Pal et al 43 In the present study, we found low agreement between abnormal ECG patterns and echocardiographic abnormalities. Landau et al 44 also showed a poor correlation between ECG and echocardiographic abnormalities. The fact that a normal echocardiogram does not rule out an abnormal ECG, and vice versa, is not surprising.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A study by van der Pal et al 43 In the present study, we found low agreement between abnormal ECG patterns and echocardiographic abnormalities. Landau et al 44 also showed a poor correlation between ECG and echocardiographic abnormalities. The fact that a normal echocardiogram does not rule out an abnormal ECG, and vice versa, is not surprising.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, we found low agreement between abnormal ECG patterns and echocardiographic abnormalities. Landau et al . also showed a poor correlation between ECG and echocardiographic abnormalities.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies performed at our center reported an extremely low rate of significant echocardiographic findings in subjects who were referred to echocardiography because of clinical or echocardiographic findings and in subjects in whom echocardiography was performed routinely [7,8] . This was in contrast to a study performed by Gray et al [12] in which a much higher rate of findings was reported, although most of these were considered insignificant.…”
Section: Discussionmentioning
confidence: 83%
“…The present study demonstrated that the rate of significant findings on echocardiography in healthy young subjects is similar to previous reports, although according to the criteria employed, it may be considered cost-effective. The different rate of findings between the tests performed because of physical or electrocardiographic findings and those performed routinely is clinically important as it may serve as preliminary evidence for the importance of the physical examination and ECG in this screening process, in contrast to previous reports [8] . Despite the relatively high cost of echocardiography for screening purposes, if it is employed only for those with physical or ECG findings, it may be cost-effective.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation